2020
DOI: 10.1371/journal.pone.0233524
|View full text |Cite
|
Sign up to set email alerts
|

Site conditions for regeneration of climax species, the key for restoring moist deciduous tropical forest in Southern Vietnam

Abstract: Understanding the requirements and tolerances of the seedlings of climax species is fundamental for tropical forest restoration. This study investigates how the presence and abundance of seedlings of a previously dominant, now threatened species (Dipterocapus dyeri Pierre), varies across a range of environmental conditions. Dipterocapus dyeri seedling abundance and site characteristics were recorded at 122 observation points (4 m 2) at nine clusters from two sites. Seedling presence (p = 0.065) and abundance v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…The D. gracilis is also a large-seeded tropical climax species with recalcitrant seeds, indicating that it is shade-tolerant. Furthermore, our finding also supported a previous study that concluded that the Dipterocarpus with latesuccessional tropical seedlings is the most shade-tolerant genus in Dipterocarpaceae family (Do et al 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The D. gracilis is also a large-seeded tropical climax species with recalcitrant seeds, indicating that it is shade-tolerant. Furthermore, our finding also supported a previous study that concluded that the Dipterocarpus with latesuccessional tropical seedlings is the most shade-tolerant genus in Dipterocarpaceae family (Do et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Inbreeding depression can occur in Dipterocarpaceae at all stages of development, including seed formation and germination, seedling development, and sapling establishment (Tsumura 2011). On the other hand, the dry soil, high temperature, and increased water loss through extensive leaf areas of the seedling of particular species are likely to be disadvantageous in wide canopy gaps (O'Brien et al 2013;Do et al 2020), as also indicated in this study. Furthermore, being intolerant to water stress, Dipterocarpus spp., a C3 plant (Raes et al 2014), has low photosynthetic efficiency.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The heavy, dense canopy and lack of parent trees are thought to be the cause of the small number of this keruing in the seedling stage. Do et al (2020) found substantial mortality for D. kerii seedlings at low light intensity. Another study on D. alatus conducted by Dongsansuk et al (2020) showed the high survival of seedlings on 50% light intensity compared to 10%, 30%, and 100%.…”
Section: Seedling Stagementioning
confidence: 85%
“…According to Steur et al (2020), the presence of local light variation may influence the growth and abundance of herbaceous layers, young trees, and seedlings. Furthermore, Do et al (2020) also stated that the forest canopy density influences the availability of forest floor light and varies over time as the forest develops. In old-growth tropical forests, light competition significantly impacts seedling's recruitment (Born et al 2015).…”
Section: Seedling Stagementioning
confidence: 99%